ETHNOMATHEMATICS-BASED LEARNING OF THE EARTH BALL MONUMENT FOR STUDENTS OF CLASS VII OF SMP NEGERI 2 WERMAKTIAN - Manutmasa, Hawila Dorenci; Samuel Urath; Yoseph Watratan (Samudra Publisher, 2025)
Ethnomathematics-based learning is currently highly relevant and aligns well with the students' environmental context. This approach facilitates learning by connecting with students’ experiences and perceptions. This study aims to examine the improvement in learning outcomes of Grade VII students at SMPN 2 Wermaktian through ethnomathematics-based learning centered on the